Perancangan Sistem Produksi Dengan Verifikasi Keamanan Data Di PT. Dynalite Investmen Mandiri Indonesia Berbasis Web - Erliyani, Ita; Faizi, Idham Noor; Subandi, Ulfah Hartini (Teknik Informatika Fakultas Ilmu Komputer, 2023)
Currently, high-speed technology, especially computers based on internet technology, and after reviewing the results of PT. Dynalite Investment Mandiri Indonesia found that companies often lose data because the existing file system still uses written media which is then entered into Microsoft Excel, so the data we receive is sometimes inaccurate and not real-time. Based on the problems that have been described, the authors are interested in conducting research on designing production systems with information security controls at PT. Web-based Dynalite Investment Mandiri Indonesia. The design of this system is based on observations, interviews, literature research, SDLC (System Development Life Cycle) analysis methods, and UML (Unified Modeling Language). The results of the author's research are archive websites using PHP (Hypertext Preprocessor) and MySQL as the database and Bootstrap (HTML, CSS, JavaScript) as the user interface. Users of this website include administrators, managers, and directors. We hope that this website can help system administrators in the documentation process.